Characterization of Plasmodium falciparum 6-Phosphogluconate Dehydrogenase as an Antimalarial Drug Target. Issue 21 (19th October 2018) - Haeussler, Kristina; Fritz-Wolf, Karin; Reichmann, Max; Rahlfs, Stefan; Becker, Katja
Abstract: The enzyme 6-phosphogluconate dehydrogenase (6PGD) of the malaria parasite Plasmodium falciparum catalyzes the third step of the pentose phosphate pathway converting 6-phosphogluconate (6PG) to ribulose 5-phosphate. The NADPH produced by 6PGD is crucial for antioxidant defense and redox regulation, and ribose 5-phosphate is essential for DNA and RNA synthesis in the rapidly growing parasite. Thus, 6PGD represents an attractive antimalarial drug target. In this study, we present the X-ray structures of Pf 6PGD in native form as well as in complex with 6PG or nicotinamide adenine dinucleotide phosphate (NADP + ) at resolutions of 2.8, 1.9, and 2.9 Å, respectively. The overall structure of the protein is similar to structures of 6PGDs from other species; however, a flexible loop close to the active site rearranges upon binding of 6PG and likely regulates the conformation of the cofactor NADP + . Upon binding of 6PG, the active site loop adopts a closed conformation. In the absence of 6PG, the loop opens and NADP + is bound in a waiting position, indicating that the cofactor and 6PG bind independently from each other. This sequential binding mechanism was supported by kinetic studies on the homodimeric wild-type Pf 6PGD. Furthermore, the function of the Plasmodium -specific residue W104L mutant was characterized by site-directed mutagenesis. Notably, the activity of Pf 6PGD was found to be post-translationally redox regulated via S -nitrosylation, and screening the Medicines for Malaria Venture Malaria Box identified several compounds with IC50 s in the low micromolar range. Together with the three-dimensional structure of the protein, this is a promising starting point for further drug discovery approaches. Graphical Abstract: Highlights: Pf 6PGD was recombinantly produced and kinetically characterized. Three X-ray structures—apo form, in complex with 6PG and NADP + —were obtained. A loop near the active site moves upon 6PG binding and adjusts the binding of NADP + . Pf 6PGD is likely to be redox regulated via protein S -nitrosylation. Its central role as a NADPH producer makes Pf 6PGD a potential drug target.